2013
DOI: 10.1136/bjsports-2012-091880
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence in physically active women and female athletes

Abstract: A literature review was performed on the topic of urinary incontinence during physical activity and sports. This paper reviews the prevalence, risk factors, pathophysiology and treatment modalities of urinary incontinence in physically active women and female athletes. Urinary incontinence affects women of all ages, including top female athletes, but is often under-reported. The highest prevalence of urinary incontinence is reported in those participating in high impact sports. Pelvic floor muscle training is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
1
20

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 56 publications
3
64
1
20
Order By: Relevance
“…Studies investigating elite athletes have found a high prevalence of SUI, particularly in those engaging in high-impact exercises involving jumping [5]. However, in long-term follow-up studies, elite athletes were not found to have a higher prevalence of SUI compared with controls [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating elite athletes have found a high prevalence of SUI, particularly in those engaging in high-impact exercises involving jumping [5]. However, in long-term follow-up studies, elite athletes were not found to have a higher prevalence of SUI compared with controls [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Os exercícios físicos de alto impacto podem ocasionar em aumento excessivo na pressão intraabdominal, podendo sobrecarregar os órgãos pélvicos, empurrando-os para baixo, ocasionando danos aos músculos responsáveis pelo suporte desses órgãos6. A prevalência dos exercícios de alto impacto pode variar de 28% a 80% 16 .…”
Section: Discussionunclassified
“…Literature proves that sports practice of high impact is related to the occurrence of pelvic floor dysfunctions, such as UI [21][22]. Reis et al [13] affirms that among the sports modalities of high impact, volleyball belongs to the ones that most intensively exert a direct influence on the pelvic floor of the athletes.…”
Section: Discussionmentioning
confidence: 99%